(untitled) (ModaPalavra e-periódico, 2018)
This article is the record of an experimental practice performed on textile substrate, aiming the manipulation of surfaces in mutable, flexible and transient projects. The concept was constructed from reflections on the traditional ways of using objects, in privacy situations, and the interaction between interior and exterior. The constructional method used was the Miura-ori and the process was handcrafted. As a result, we present the object "membrane" that, in a sensorial and poetic way, was handled in different situations and formats, proving the possible transitoriness of the textile surfaces.